Complementary Feeding Initiation Timing, Responsive Feeding Practices, and the Incidence of Underweight among 6-23 Months Children - Ummu Kalsum; justiyulfah Syah; Andi Sri Rahayu Kasma (Ikatan Sarjana Gizi Indonesia (ISAGI), 2026)
Underweight remains a multidimensional public health problem among young children, influenced by various factors, including suboptimal feeding practices. Evidence on the role of complementary feeding initiation timing and responsive feeding in underweight remains inconsistent, particularly in low-resource settings. This study aimed to examine the association of complementary feeding initiation timing and responsive feeding practices with underweight among children aged 6–23 months. A cross-sectional study was conducted among 86 children under two years of age selected using simple random sampling. Data were collected through structured interviews to assess feeding practices and anthropometric measurements to determine nutritional status. Underweight was defined based on weight-for-age indicators. The findings showed that neither the timing of complementary feeding initiation nor responsive feeding practices were significantly associated with underweight among children aged 6–24 months. These findings suggest that underweight in this population may be influenced by other underlying factors beyond feeding timing and caregiver practices. Comprehensive, multisectoral interventions addressing broader determinants of child nutrition are needed to effectively reduce underweight prevalence.